Transforming the Master Narrative. - Lawless, Elaine J. (Frontiers: A Journal of Women Studies, 2003)
This article illustrates the ways in which women in the pulpit shift the religious subject and challenge the male-identified religious master narrative by their presence, voice, and experiences. Religions in which only men enter the primary sanctuary and where only men are allowed to pray and speak are intentionally naming the religious subject as male. Modifications to this model occur in religious contexts where women are allowed in the sanctuary but where male clergy and religious potency are still endorsed, as evidenced in clerical garb vested with the inscriptions of power and authority, and (again) where praying, speaking, and preaching are restricted to men. Yet often in the most restrictive of religious contexts, when the female subject makes her presence known she forces a shift in the religious subject. These female subjects, then, bring not only subjectivity to the religious subject, they also bring their female experiences and wed them back into the subject of religion. This both changes the subject and transforms the master narrative in one discursive moment.